Fabrication of photothermal nature-inspired materials application on highly solar steam generation - Nguyen, Minh Tuan (2020)
Clean freshwater plays an essential role in human life and social development, which relates closely to many aspects such as potable water, food-producing, environment protection, ecological equilibrium, and so on. As we known that 70% of Earth’s surface is covered by water, but only about 1.7% of that is freshwater being suitable for consumption. Water scarcity has been considered as one of the most serious risks in the world, which is originated from the unequal distribution of water over time and place on Earth. Besides that waste, pollution, and unsustainable consumption are also known as causes from human activities leading to water scarcity. Developing nanostructured materials-based methods for converting saltwater into freshwater has attracted the broad attention of the scientist, which is a potential approach to contribute to reducing consequences of water scarcity. Thermal distillation method makes steam from salt water sources, and the condensation then generates the liquid phase of freshwater